A Randomized Controlled Trial on the Efficacy of Xinnaoning Capsule in the Treatment of CSAP Complicated With Qi Stagnation and Blood Stasis Syndrome - Li, Jing; Zhang, Ping; Zhang, Ying; Wang, Haiyun; Wu, Liqi; Zhao, Junnan; Liu, Yue; Zeng, Wenying; Guo, Renzhen; Mei, Jun; Xu, Fengqin (Frontiers in Cardiovascular Medicine, 2022)
Objective This study was designed to explore the efficacy and safety of Xinnaoning Capsule (XNNC) in the treatment of patients with chronic stable angina pectoris (CSAP) complicated with Qi stagnation and blood stasis syndrome. Methods A total of 240 patients with CSAP complicated with Qi stagnation and blood stasis syndrome who met the inclusion criteria were enrolled from 8 medical centers across China. The trial treatment lasted 14 weeks, including a 2-week lead-in period and a 12-week double-blind treatment period. Patients in the experimental group were treated with XNNC, while patients in the control group were treated with placebos. Thereafter, examinations were conducted on the efficacy of angina pectoris before and after treatment and the relief of symptoms, followed by the recording of grading changes in angina severity, changes in the number of angina pectoris, and the amount of taken nitroglycerin. Finally, adverse events were assessed. Results Compared with the control group, the total score and the effective rate of angina pectoris were significantly increased in the experimental group, accompanied by the statistically significant improvement in the severity of angina pectoris (all p < 0.05). Furthermore, there was no statistically significant difference in the adverse events and serious adverse events between the experimental group and the control group (p = 1.0000) before and after treatment. Conclusion XNNC is a safe and effective medicine for patients with CSAP complicated with Qi stagnation and blood stasis syndrome.